INTRODUCTION AND UTILIZATION OF A SOLAR POWERED HYDROPONIC AUTOMATIC NUTRITION SYSTEM (AIROPONIK) AS A SMART AGRICULTURAL SOLUTION FOR HOUSEHOLD-SCALE FARMING IN PANDEREJO VILLAGE, GEMPOL DISTRICT, PASURUAN - Setiawan, Muhammad Aldo; Prastio, Rizki Putra; Putra, Saddam Al Fattah; Masyhur, Abdullah Al; Saepudin, Muhammad Sandi (Universitas Airlangga, 2025)
This community service activity focuses on implementing an automatic nutrient control system called Airoponik (Airlangga Robot Hydroponic) for hydroponic farmer groups in Panderejo hamlet, Gempol, East Java. The system was developed to address the challenges in maintaining precise nutrient concentrations in hydroponic systems, which is crucial for optimal plant growth. The Airoponik prototype integrates Total Dissolved Solids (TDS) sensors, temperature sensors, and an automated control system based on ESP32 microcontroller, enabling automatic adjustment of nutrient levels within a ±5% tolerance range. The implementation process included prototype development, laboratory testing, and technology dissemination to the community. Testing results demonstrated successful nutrient control at various target levels (400, 700, and 1000 ppm). In addition to the functionality of the Airoponik system, its compact, suitcase-style design facilitates easy installation and adjustment of the device in space-constrained environments. To ensure effectiveness, observations revealed that the aeroponic system required only 43% of the maintenance time compared to conventional systems. The community response was highly positive, with 88% of participants expressing interest in adopting the technology, and achieving dissemination impact scores of 4.2/5.0. The integration with existing solar-powered hydroponic systems proved successful, providing a sustainable solution for automated nutrient management without dependence on grid electricity.